1986
DOI: 10.7164/antibiotics.39.1605
|View full text |Cite
|
Sign up to set email alerts
|

The structure of vermistatin, a new metabolite from Penicillium vermiculatum.

Abstract: Separation of metabolites of Penicillium vermiculatum DANG present in the cultivation medium afforded three new antibiotics; vermiculinel), vermistatin2) and vermicillin3) . The structure of vermiculine, a macrolide dilactone has already been solved by X-ray diffraction analysis". This paper presents the structure elucidation of the second compound of this series, vermistatin.In our previous paper2) we reported the isolation, antibiotic and cytotoxic activity of vermistatin (1); it is a white crystalline compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 12 publications
6
41
0
Order By: Relevance
“…By establishing a convenient assay system using C. albicans and miconazole, four funicone-related compounds including new actofunicone were isolated from the culture broth of T. flavus FKI-0076. As we expected, the funicones did not inhibit the growth of C. albicans even at was reported that they showed very weak antifungal activity7, 8,11). However, the funicones showed dosedependent anti-C. albicans activity in combination with although miconazole alone gave no effect on the fungal growth at the concentration.…”
Section: Discussionmentioning
confidence: 58%
“…By establishing a convenient assay system using C. albicans and miconazole, four funicone-related compounds including new actofunicone were isolated from the culture broth of T. flavus FKI-0076. As we expected, the funicones did not inhibit the growth of C. albicans even at was reported that they showed very weak antifungal activity7, 8,11). However, the funicones showed dosedependent anti-C. albicans activity in combination with although miconazole alone gave no effect on the fungal growth at the concentration.…”
Section: Discussionmentioning
confidence: 58%
“…chiana (40). Desmethyldehydroaltenusin (14)4 is the second metabolite isolated in the form of its acetate (15). The sequential loss of three molecules of ketene from the parent ion (CZ0Hl6o9) in the mass spectrum affords an ion corresponding to a molecular formula C14H1006, which differs from that of dehydroaltenusin (12) (11) and dehydroaltenusin (12), and the previously unreported desmethyldehydroaltenusin (14), may be envisaged as proceeding by cyclization of a heptaketide precursor to give the biphenyl derivative shown in Scheme 2.…”
Section: Discussionmentioning
confidence: 99%
“…'of Talaromyces (4-10) other than T. jlavus. The imperfect (conidial) state of T. jlavus, Penicillium dangeardii Pitt, produces three metabolites that are reported to show antibiotic activity (11)(12)(13)(14)(15). The isolation of a water soluble compound possessing antibiotic activity from T. jlavus has recently been reported (16).…”
Section: Introductionmentioning
confidence: 99%
“…IR spectra were recorded on a Shimadzu 435-U-04 spectrophotometer (KBr pellets). 1 H and 13 C NMR spectra were obtained using Bruker DRX-300 Advance spectrometer in DMSO-d 6 or CDCl 3 using TMS as an internal reference. Melting points were determined in open capillary tubes in a Stuart BI Branstead Electrothermal Cat No: IA9200 apparatus and uncorrected.…”
Section: Methodsmentioning
confidence: 99%
“…Typical examples are are fuscinarin (1) 1 , typhaphthalide (2) 2 , catalpalactone (3) 3 , alcyopterosin E (4) 4 , (+)-spirolaxine (5) 5 , vermistatin (6) 6 , rubiginone-H (7) 7 , (-)-hydrastine (8) 8 , isopestacin (9) 9 , and cryphonectricacid (10) 10 .…”
Section: Introductionmentioning
confidence: 99%